The Effect of Work Discipline on Job Satisfaction Mediated by Rewards in MSME Convection in Pasuruan Regency - Lailatul Ula; Jeziano Rizkita Boyas; Wahyu Eko Pujianto; Cynthia Eka Violita (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study examines the effect of work discipline on employee job satisfaction in convection UMKM in Pasuruan Regency, with reward as a mediating variable. Quantitative methods were used to collect data through questionnaires distributed to 160 employees. The results of the analysis show that work discipline has a significant positive effect on job satisfaction, and that reward can mediate the relationship. These findings highlight the importance of implementing a balanced reward system to improve employee performance and job satisfaction.